2016
DOI: 10.1021/acs.jpcb.6b04089
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Catalysis: A Computational Study of Tetrahedral Intermediates and Inhibitory Adducts

Abstract: Peptide boronic acids and peptidyl trifluoromethyl ketones (TFKs) inhibit serine proteases by forming monoanionic, tetrahedral adducts to serine in the active sites. Investigators regard these adducts as analogs of monoanionic, tetrahedral intermediates. Density functional theory (DFT) calculations and fractional charge analysis show that tetrahedral adducts of model peptidyl TFKs are structurally and electrostatically very similar to corresponding tetrahedral intermediates. In contrast, the DFT calculations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
2
15
1
Order By: Relevance
“…In our earlier NMR studies we demonstrated the existence of the above mentioned LBHB between H51 and D75 of the catalytic triad in the transition state of DENV2 NS2B:NS3pro with substrate-analogue boronic acid inhibitor Bz-Nle-Lys-Arg-Arg-B(OH)2, (compound I, Table 1) [20]. To our knowledge, this is the first time the existence of a LBHB type complex in serine proteases, as has been predicted [12], could be demonstrated by NMR spectroscopy in a biological system. The unusual large low-filed shift of N δ1 H (19.93 ppm) of H51 combined with a N-H splitting of only 52 Hz clearly indicated the presence of LBHB [20].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…In our earlier NMR studies we demonstrated the existence of the above mentioned LBHB between H51 and D75 of the catalytic triad in the transition state of DENV2 NS2B:NS3pro with substrate-analogue boronic acid inhibitor Bz-Nle-Lys-Arg-Arg-B(OH)2, (compound I, Table 1) [20]. To our knowledge, this is the first time the existence of a LBHB type complex in serine proteases, as has been predicted [12], could be demonstrated by NMR spectroscopy in a biological system. The unusual large low-filed shift of N δ1 H (19.93 ppm) of H51 combined with a N-H splitting of only 52 Hz clearly indicated the presence of LBHB [20].…”
Section: Introductionsupporting
confidence: 67%
“…The exact nature of the hydrogen bonds in the catalytic triad is of importance in order to understand the mechanism. It has been suggested that the aspartate hydrogen bond to the histidine is a delocalized low barrier hydrogen bond (LBHB) [11,12]. LBHB is thus important to the understanding of the structure of the tetrahedral transition state for the functioning enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QM/MM optimization of non-covalent complex of hAChE with TFK in the active site obtained by molecular docking leads to size expansion of the active site necessary to accommodate the inhibitor and lower energy barrier for formation of covalent adduct. Traditionally, resulting hemiketals are called "transition state analogs", though practically they are rather analogs of tetrahedral intermediate of AChE-catalyzed ester hydrolysis [55,56]. Hemiketal configuration is very close for TFK and TMTFA, with the only difference that trimethyl ammonium group of TMTFA is 0.6 Å closer to Glu202 than tert-butyl moiety of TMTFA.…”
Section: Molecular Modeling Of Interaction Between Tfk and Achementioning
confidence: 99%
“…These two fluorinated moieties exhibit another important characteristic; they can easily hydrate, depending on the nature of the amino acids they are bound to, forming very stable gem -diols which mimic the tetrahedral adduct of the transition-state of the enzyme-substrate hydrolysis mechanism ( Figure 1 ). Therefore, the resulting PFMKs may also act exclusively as transition-state competitive analogues leading to rapidly reversible competitive inhibition [ 5 , 6 ]. In most cases, a mixture of the two FMK forms (i.e., carbonyl and hydrated) in different ratio is observed in solution, and a dual inhibition mechanism of the PFMKs is detected consequently.…”
Section: Introductionmentioning
confidence: 99%